2010
DOI: 10.1200/jop.2010.000033
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led, Interdisciplinary Model for Delivery of Supportive Care in the Ambulatory Cancer Clinic Setting

Abstract: Purpose: To describe a pharmacist-led, interdisciplinary method of care delivery begun at the University of North Carolina. We describe the characteristics of the population seen and the role of the individual members of the interdisciplinary team, and provide an early analysis of the program's impact on symptom improvement. Methods:A supportive care consultation service was begun at the University of North Carolina Hospitals to serve adult outpatients with cancer undergoing treatment or follow-up. Patients da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…16,22,23 Wilson et al 23 reported that implementation of pharmacist recommendations in a palliative care setting was 1 of the strongest predictors of patients achieving desired outcomes. Because the purpose of this study was to evaluate the impact of a previsit pharmacist review, and in an attempt to evaluate an intervention that could feasibly be added to other current pharmacist clinic responsibilities, the pharmacists did not implement any of the intervention recommendations but rather deferred implementation to the prescriber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,22,23 Wilson et al 23 reported that implementation of pharmacist recommendations in a palliative care setting was 1 of the strongest predictors of patients achieving desired outcomes. Because the purpose of this study was to evaluate the impact of a previsit pharmacist review, and in an attempt to evaluate an intervention that could feasibly be added to other current pharmacist clinic responsibilities, the pharmacists did not implement any of the intervention recommendations but rather deferred implementation to the prescriber.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature on pharmacist engagement in chronic pain management is limited to specialty care settings (eg, palliative care), investigations of patient-centered medical home designation, or descriptive reports. 15,16,[22][23][24][25] To our knowledge, this is the first published study of the impact of a pharmacist-led intervention focused on comprehensive chronic pain management in a family medicine setting. The purpose of this study was to evaluate the impact of a previsit pharmacist review of highrisk patients treated with opioids for chronic noncancer pain for compliance with CDC recommendations at a family medicine residency clinic.…”
mentioning
confidence: 99%
“…The progressive use of oncology pharmacists at the Duke and University of North Carolina Lineberger/North Carolina Cancer Hospitals has proven the value of pharmacists in optimizing healthcare efficiency in the outpatient setting. [9][10][11][12] In these facilities, pharmacists have developed over 200 chemotherapy order sets and initiated outpatient supportive care services focusing on patient education and cancer symptom management. These services have effectively reduced the time physicians spend writing medication orders.…”
Section: No (%) Respondents (N = 26)mentioning
confidence: 99%
“…3 Similar strategies are also employed in the United States; for example, at the University of north carolina, a pharmacist-led team focuses on pain management for oncology patients. 4 Under the collaborative practice agreement, the pharmacist prescribes medications, including narcotics. the resulting interventions have improved symptom scores and benefitted the patient population in this facility.…”
mentioning
confidence: 99%
“…the resulting interventions have improved symptom scores and benefitted the patient population in this facility. 4 the idea of pharmacists prescribing controlled drugs has progressed one step further in the United Kingdom. In 1997, the UK government established a review of prescription supplies and administration of medicines.…”
mentioning
confidence: 99%